2011
DOI: 10.3354/dao02400
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Acanthaster planci with thiosulfate-citrate-bile-sucrose agar (TCBS). II. Histopathological changes

Abstract: ABSTRACT:We assessed histological changes in the tissues of the crown-of-thorns starfish Acanthaster planci (COTS) after injection of thiosulfate-citrate-bile-sucrose agar (TCBS) which was used as a disease inducer (potential outbreak control method), by conventional and scanning electron microscopy. Digestive glands were processed and stained with hematoxylin and eosin to describe the histological architecture of the intestinal epithelium. Subsequently comparison of healthy versus infected tissues and Gram st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Interestingly, NCBI Blast results placed V. echinoideorum with the highest total-score for of the top 5 ASVs with the largest fold-change when comparing Naïve to Exposed sea stars. Additionally, a 2011 study focusing on population control methods of the Crown of thorns Sea Star, Acanthaster planci, used a thiosulfate-citrate-bile-sucrose agar (TCBS) to selectively stimulate the growth of Vibrionaceae species (Rivera-Posada et al, 2011a;Rivera-Posada et al, 2011b). Not only did the TCBS stimulation of Vibrionaceae species elicit SSW-like signs and mortality, but a follow up study in 2012 demonstrated an interspecies transmissibility of the TCBS-induced disease between different species of asteroids (Caballes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NCBI Blast results placed V. echinoideorum with the highest total-score for of the top 5 ASVs with the largest fold-change when comparing Naïve to Exposed sea stars. Additionally, a 2011 study focusing on population control methods of the Crown of thorns Sea Star, Acanthaster planci, used a thiosulfate-citrate-bile-sucrose agar (TCBS) to selectively stimulate the growth of Vibrionaceae species (Rivera-Posada et al, 2011a;Rivera-Posada et al, 2011b). Not only did the TCBS stimulation of Vibrionaceae species elicit SSW-like signs and mortality, but a follow up study in 2012 demonstrated an interspecies transmissibility of the TCBS-induced disease between different species of asteroids (Caballes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are likely to be significant constraints on energy investment for CoTS towards the end of outbreaks following selective depletion of preferred coral prey (e.g., Acropora) if not comprehensive coral loss [178]. If crown-of-thorns starfish continue to invest disproportionately into immune defense even when prey are scarce, energy reserves will be depleted even more rapidly, thereby making individuals even more prone to disease [180,181].…”
Section: Question 6 (Adults)-what Is the Rate Of Predation On Adults mentioning
confidence: 99%
“…1C,D). These lesions could be a result of the lysis of connective tissues induced by opportunistic bacteria as shown in histopathological analyses of diseased A. planci (Rivera-Posada et al 2011b).…”
Section: Resultsmentioning
confidence: 99%